It is simply as stated in the question. Without information about a or b, the expression cannot be simplified nor evaluated.
p=b+3a+c p-3a-c=b+3a-3a+c-c p-3a-c=b b=p-3a-c
The given expression can be simplified to: 3b-a
If a + b = 6, what is the value of 3a + 3b?
This expression can be factored. ab + 3a + b2 + 3b = a(b + 3) + b(b + 3) = (a + b)(b + 3)
3a+ax+3b+bx = 3(a+b)+(a+b)x = (a+b)(3+x)
3ab + 3ac + 2b2 + 2bc = 3a(b + c) + 2b(b + c) = (3a + 2b)(b + c)
a + b + c = 180 b = 3a c = 5a Substituting the values of b and c into the first equation. a + 3a + 5a = 180 or 9a = 180 so that a = 20 then b = 3a = 3*20 = 60 and c = 5a = 5*20 = 100
-2a plus 3b
7a minus 2, if "3a-2" means 3a minus 2. 3a plus 1 and 1-3rd in parenthesis times 3a, if "3a-2" means 3a squared. a plus 3a squared plus 3a = 1-3rd times 3a plus 3a times 3a plus 1 times 3a = 3a plus 1 and 1-3rd in parenthesis times 3a
Thenx = (c - b) / 3a
a = 15.
Collect the terms in a, then the terms in b, getting 6a - 3a + 2b + 5b which simplifies to 3a + 7b. Gettit?
6a square plus b square
That factors to (b + 3)(a + c)
(x + 3)(a + b)
= a + b - 2
From your description, I get: a + b + c = 180b - 3a c = 5a You have two equations and three unknowns, which is unsolvable.
a(3+b)+c(3+b) * * * * * This is easy to finish: . . . = (a + c)(3 + b).
(b + 3)(a + c)